Morphological and Proreomic Analysis of Mas Cotek (Ficus Deltoidea) Population of Peninsular Malaysia - Rogini Sivalingam (2015)
This study is the first report which was conducted to analyze the genetic variability in different varieties of Ficus deltoidea using isoenzymes as a marker which was profiled by using Sodium Dodecyl Sulphate Polyacrylamide Gel Electrophoresis, SDS-PAGE technique. From the isoenzyme profile, a dendogram was developed to identify the phylogenetic relationship among the varieties of F. deltoidea. From this study, three major clusters of the varieties were identified. The first two major clusters contain two sub-cluster or chucks each. The phenotypic variations in F. deltoidea varieties had also been identified using leaf morphological characteristics of the different accessions. In this study, the phenotypic variations among different accessions of F. deltoidea had been identified and different new accessions in certain varieties has been predicted.